Canonical Institution of Autocephaly and Diaspora. The Recent Conflict between the Jerusalem Patriarchate and the Romanian Patriarchate - Mihai L. Constantinescu, Iulian (Forum Theologicum Sardicense, 2025)
In this study, we will evaluate the canonical doctrine of the Orthodox Church from an ecclesiological-canonical and historical perspective regarding autocephaly. We will examine the constitution of local autocephalous Churches on canonical bases, the issue of proclaiming autocephaly, and the jurisdiction of autocephalous Churches over their ecclesiastical units in the diaspora. Additionally, we will emphasize the contribution of Romanian theologians and canonists to the inter-Orthodox dialogue on current canonical issues. This study builds upon my previous work, “The Principle of Ecclesiastical Autocephaly and the Problems of Inter-Orthodox Jurisdiction: An Actual Ecclesiological and Canonical Contribution” (2008), to discuss the issue of autocephaly, canonical territory, and the rights of autocephalous patriarchies and their jurisdiction over their own diaspora. These are issues of great relevance today with significant canonical implications for inter-Orthodox relations. This very issue, along with other local problems of a different nature, was at the root of the ecclesiastical conflict between the historical Greek Patriarchate of Jerusalem and the Romanian Patriarchate, a conflict that led to the breaking of communion with the Romanian patriarch and the defrocking of the Romanian Patriarchate’s representative in Jerusalem.